Perbandingan Model Komisi Yudisial Republik Indonesia Dengan Komisi Yudisial Perancis - Suparto Suparto (UIR Law Review, 2019)
The standing of the Judiciary Commitee, thus structurally it wascreated on the same level with the Supreme Court and the Constitutional Court.Even so, the nature of the Judiciary Committee is an auxiliary to the judiciary bodies.Even if the function of the Judiciary Committee is related with Judiciary power, yet it is not the actor of the Judiciary power, but an institution to uphold the code of ethics. Aside from that, the Judiciary Committee is not involved in the organization, human resources, administration, and financial matters of the judges. This is different with the similar committees in the Europe, i.e. France. The France Council for Judiciary has the authority in the technical field as well as the policy making in the judiciary bodies. The judciary committees of the France and Europe in general has the authority in the management of the organization, budgeting, and administration of the courts, including on promotion, rotation, recruitment, and the giving of a sanction to the judges. The Supreme Court itself focuses on the trial conduct, and does not handles the administration and the organization of the court.